Physeal-Sparing Anterior Cruciate Ligament Reconstruction For Skeletally Immature Knee: A Case Report - Tu Bagus Adnan Angga Prawira; I Gusti Ngurah Wien Aryana; I Gusti Made Febry Siswanto (International Medical Journal Corp. Ltd, 2024)
Introduction : ACL injuries are common in the knee and often caused by non-contact sports or dynamic valgus knee movements. There has been an increase in competitive sports at younger ages, resulting in higher levels of competition and greater recognition of sports injuries by coaches and specialists. Case Report : Patient is a 14 year old woman with the initials RNF came to the emergency room of the hospital with complaints of pain in the right knee accompanied by a feeling of instability after suffering an injury while playing football with the mechanism of injury: when the patient was running and was about to change direction by supporting her right leg, suddenly the patient felt pain and there was a sound in the right knee area. After history, physical examination, and supporting test, diagnosis was made as complete ACL tear and surgery was planned in the form of ACL reconstruction using the physeal sparing technique. Discussion : The risk of ACL damage is greater in young and active individuals. The physeal-sparing technique is a relatively safe approach with few complications. It reduces knee pain at the donor site and lowers the risk of nerve damage. This method also reduces the risk of joint damage after physical activity. Young athletes who returned to sports after ACL reconstruction showed a much higher rate of injury, with a 30 to 40 times greater risk of ACL injury compared to uninjured youth. Effective communication among patient and specialist therapeutic is crucial for a successful surgery and safe return to sports and daily activities. Conclusion : Full ACL reconstruction using a physeal-sparing technique in young patients is a safe method that protects the growth plate and avoids the complications. However, further research is needed to determine the long-term effectiveness of this approach in treating ACL injuries in young patients.